The effect of land-use intensity on the species-area relationship of plants within temperate grasslands - Bolliger, Ralph; Neuenkamp, Lena; Prati, Daniel; Fischer, Markus (Basic and applied ecology, 2025)
It is well-known that land-use intensity directly affects plant-species richness in temperate grasslands. However, the effect of land-use intensity on plant distribution at small spatial scales, as indicated by the slope of the species-area relationship, is rarely investigated. We tested whether the species-area relationship is directly affected by land-use intensity or indirectly via plant species richness. We studied the species-area relationship by measuring the rate of species richness increase between different plot sizes. We used nested quadrats of 0.2 by 0.2 m and 1 m by 1 m within each of 147 4 × 4 m plots of managed grasslands in three German regions in 2017 or 2018. With linear models, we found that the different components of land use (mowing, grazing and fertilization) had various direct effects on the species-area relationship. Mowing reduced the slope of the species-area relationship, indicating a more even distribution of plant species within plots at higher land-use intensity. Fertilisation did not significantly affect the slope of the species-area relationship, while grazing increased it. As a result of these different component effects, overall land-use intensity did not affect the species-area relationship directly. In addition, we used structural equation modelling to assess the direct and indirect effect of land-use intensity on the species-area relationship. We found that land-use intensity had only a negative indirect effect on the species-area relationship through a negative effect on species richness. An additional analysis with land-use components, mowing and grazing, confirmed the indirect negative effect of land-use on species-area relationship. Our results underline the importance of testing direct and indirect effects of land-use intensity. Furthermore, we show the importance of considering regional environmental differences before being able to generalize land-use effects on plant species heterogeneity.